KONSEP SYAFA’AT DALAM PERSPEKTIF AL-QUR’AN DAN AL-HADIS - Nurliana Damanik (SHAHIH (Jurnal Ilmu Kewahyuan), 2018)
“Intercession applies to people who do not get the permission and pleasure of Allah, ie the disbelievers. While the verses which state the intercession in the Hereafter, apply to those who are given permission and Allah's approval. God declares that all intercession is His right. No one is entitled to intercede except for those whom He permits to be interceded and He is pleased with his words and deeds.”